2004
DOI: 10.1542/peds.2003-0264-f
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone in the Treatment of Disruptive Behavioral Symptoms in Children With Autistic and Other Pervasive Developmental Disorders

Abstract: ABSTRACT. Objective. To investigate the efficacy and safety of risperidone for the treatment of disruptive behavioral symptoms in children with autism and other pervasive developmental disorders (PDD).Methods. In this 8-week, randomized, double-blind, placebo-controlled trial, risperidone/placebo solution (0.01-0.06 mg/kg/day) was administered to 79 children who were aged 5 to 12 years and had PDD. Behavioral symptoms were assessed using the Aberrant Behavior Checklist (ABC), Nisonger Child Behavior Rating For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
286
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(307 citation statements)
references
References 18 publications
11
286
4
1
Order By: Relevance
“…[5][6][7]29 These positive effects were maintained at least during 1 year, which was the maximum period evaluated in this study. As expected from earlier trials, we found a marked increase in BMI, waist circumference and prolactin levels.…”
Section: Pharmacogenetics Of Risperidone In Autismmentioning
confidence: 68%
See 1 more Smart Citation
“…[5][6][7]29 These positive effects were maintained at least during 1 year, which was the maximum period evaluated in this study. As expected from earlier trials, we found a marked increase in BMI, waist circumference and prolactin levels.…”
Section: Pharmacogenetics Of Risperidone In Autismmentioning
confidence: 68%
“…1 According to a recent survey, 31% of children with autism spectrum disorders take an antipsychotic medication, 2 with risperidone one of the most popular atypical antipsychotics prescribed. Several open trials of risperidone in autism (reviewed in 3,4 ) and three placebo double-blind randomized controlled trials, [5][6][7] reported significant improvements in at least half of the patients evaluated. 4,8 Risperidone was shown to be well tolerated and effective in treating aggressiveness, hyperactivity, irritability, self-injurious behaviours, stereotipies, social withdrawal and lack of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Maladaptive behaviors are behaviors that interfere with everyday activities, and include self-injurious behavior, withdrawal, uncooperative behavior, aggression, and destruction of property. Although maladaptive behaviors are often exhibited by people with ASD (Aman, Lam, & CollierCrespin, 2003;Hollander, Phillips, & Yeh, 2003;Shea et al, 2004) and are noted as an associated condition in the DSM-IV definition of autism (APA, 2000), there has been relatively little research documenting their prevalence and course. A longitudinal study of 967 children with different types of intellectual disabilities reported that children with autism had higher levels of maladaptive behaviors than children with fragile × syndrome, Williams syndrome, Prader-Willi syndrome, Down syndrome, or children with an intellectual disability with no specified etiology (Tonge & Einfeld, 2003).…”
Section: Prevalence and Change In Maladaptive Behaviors In Adolescencmentioning
confidence: 99%
“…The approval was largely based on the findings from two randomized, controlled trials in 79 and 101 children with autistic disorder and severe behavioral problems. 4,5 In the larger study, children in the risperidone group had a 57% reduction in irritability compared to only a 14% reduction among children in the placebo group (p Ͻ 0.001). 4 A second atypical antipsychotic, aripiprazole, was approved in late 2009 for the same indication (irritability) in children with ASD, based on the results from two 8-week randomized, placebo-controlled trials in 98 and 218 patients.…”
Section: Introductionmentioning
confidence: 91%